2017
DOI: 10.1186/s12879-017-2794-x
|View full text |Cite
|
Sign up to set email alerts
|

Strong associations between national prevalence of various STIs suggests sexual network connectivity is a common underpinning risk factor

Abstract: BackgroundIf national peak Human Immunodeficiency Virus (HIV) prevalence is positively associated with the prevalence of other sexually transmitted infections (STIs) from before or early on in the HIV epidemics this would suggest common underlying drivers.MethodsPearson’s correlations were calculated between the prevalence of seven STIs at a country-level: chlamydia, gonorrhoea, trichomoniasis, syphilis, bacterial vaginosis, herpes simplex virus-2 (HSV-2) and HIV.ResultsThe prevalence of all the STIs was highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Populations with a higher prevalence of BV also tend to have a higher prevalence of other STIs [65]. This association has been shown between BV and HIV prevalence at the level of world regions [80], countries [65] and ethnic groups within countries (Fig.…”
Section: Network Connectivity Is a Parsimonious Explanation For The Amentioning
confidence: 85%
See 1 more Smart Citation
“…Populations with a higher prevalence of BV also tend to have a higher prevalence of other STIs [65]. This association has been shown between BV and HIV prevalence at the level of world regions [80], countries [65] and ethnic groups within countries (Fig.…”
Section: Network Connectivity Is a Parsimonious Explanation For The Amentioning
confidence: 85%
“…Since sexual network connectivity is a population-level property, ecological studies are also necessary to explore the possible explanations for variations in STI prevalence [50, 62]. Although not all studies have reached this conclusion, [63, 64] studies have generally found a positive association between STI prevalence and the prevalence of partner concurrency and/or numbers of partners per unit time [50, 52, 58, 6567].…”
Section: Individual and Couple-level Datamentioning
confidence: 99%
“…Combinations of these attributes should result in higher network connectivity in some populations than in others ( 6 , 7 ). Studies have found a correlation between markers of network connectivity and the prevalence of various major STIs ( 7 ), including N. gonorrhoeae ( 8 , 9 ). STI prevalence can also be influenced by other risk factors that can affect the probability of transmission per contact (such as male circumcision, condom use, and presence of other STIs) or the duration of infectivity (such as STI early detection and treatment efficacy) ( 10 ).…”
Section: Sti Prevalence As a Function Of Network Connectivitymentioning
confidence: 99%
“…From 2010-2011, the STI incidence for South Africa was 3.9% [7]. Kenyon and colleagues reported prevalence of syphilis and male urethral discharge in South Africa at 8.3% and 13.8% respectively [4].…”
Section: Introductionmentioning
confidence: 99%
“…The extent of the STI problem and the association with HIV transmission highlights the need to continue and strengthen prevention and control of STIs [4]. The effective treatment and control of STIs depends on screening to detect and treat STIs among the sexual partners of the STI infected patients, which is dependent on the patient-initiated PN practices using referral slips in the South African treatment protocol.…”
Section: Introductionmentioning
confidence: 99%